Nilai-Nilai yang Terkandung dalam Tradisi Perahu Baganduang Desa Lubuk Jambi Kabupaten Kuantan Singingi Provinsi Riau - Ervina Dwi Ningtyas; Yahyar Erawati (Yayasan Al-Afif, 2026)
This study examines the values embedded in the Perahu Baganduang tradition in Lubuk Jambi Village, Kuantan Singingi Regency, Riau Province. The study aims to identify and analyze religious, customary, traditional, and social values reflected in the practice of this tradition. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. The findings reveal that the Perahu Baganduang tradition has undergone a functional shift from a transportation medium to a cultural festival that preserves ancestral heritage. Religious values are evident in its implementation during Eid al-Fitr, halal bihalal activities, and the use of Moon and Star symbols symbolizing belief in the oneness of Allah Swt. Customary values appear through deliberation and consensus in determining community participation, while traditional values are reflected in the continuity of ritual practices across generations. Social values are manifested in cooperation, mutual assistance, and community solidarity. Overall, the Perahu Baganduang tradition functions as a medium for strengthening cultural identity and sustaining local wisdom within the community.